Literacy Tradition in Islamic Education in Colonial Period - Kambali Zutas (Al-Hayat Al-Istiqomah Foundation, 2017)
The tradition of literacy in Islamic education has evolved since the time of the Prophet Muhammad. This culture of reading and writing continues to evolve from time to time. The scholars and scholars of Islam have many works in enriching the intellectual treasures. Not only famous in the country but works that are far in the past is still relevant to be studied and examined more deeply. In Indonesia the tradition of literacy in Islam has started since the beginning of the spread of Islam until now. However, during the period of Indonesia's colonial experience, the literacy tradition in education was closely monitored by the colonial government. Nevertheless the scholars still work. Not a little work of this scholar to give spirit to the people and society to fight and defend the country.